f= (ab 'cd ')+(a 'b 'cd) +(a 'bc 'd)+(a 'bcd)+(ab 'cd)+(abc 'd)
Simplify the algebraic form for f as much as possible.
Sorry here is a clarification.
A B C D Output F
0 0 0 0----0
0 0 0 1----0
0 0 1 0----1
0 0 1 1----1
0 1 0 0----0
0 1 0 1----1
0 1 1 0----0
0 1 1 1----1
1 0 0 0----0
1 0 0 1----0
1 0 1 0----0
1 0 1 1----1
1 1 0 0----0
1 1 0 1----1
1 1 1 0----0
1 1 1 1----0
Would this be correct as the algebraic expression?
for output f the eg is f = (¬a.¬b.c.¬d)+(¬a.¬b.c.d) +(¬a.b.¬c.d)+(¬a.b.c.d)+(a.¬b.c.d)+(a.b.¬c.d)
+ = OR
. = AND
¬ = NOT
How do I simplify the algebraic form for f as much as possible?